A dysphoric's TALE: The relationship between the self-reported functions of autobiographical memory and symptoms of depression. Issue 9 (20th October 2016) - Grace, Lydia; Dewhurst, Stephen A.; Anderson, Rachel J.
ABSTRACT: Autobiographical memory (AM) is believed to serve self, social and directive functions; however, little is known regarding how this triad of functions operates in depression. Using the Thinking About Life Experiences questionnaire [Bluck, S., & Alea, N. (2011). Crafting the TALE: Construction of a measure to assess the functions of autobiographical remembering. Memory, 19, 470–486.; Bluck, S., Alea, N., Habermas, T., & Rubin, D. C. (2005). A TALE of three functions: The self–reported uses of autobiographical memory. Social Cognition, 23, 91–117.], two studies explored the relationship between depressive symptomology and the self-reported frequency and usefulness of AMs for self, social and directive purposes. Study 1 revealed that thinking more frequently but talking less frequently about past life events was significantly associated with higher depression scores. Recalling past events more frequently to maintain self-continuity was also significantly associated with higher depressive symptomology. However, results from Study 2 indicated that higher levels of depression were also significantly associated with less-frequent useful recollections of past life events for self-continuity purposes. Taken together, the findings suggest atypical utilisations of AM to serve self-continuity functions in depression and can be interpreted within the wider context of ruminative thought processes.